The contemporary and current reception of the Lectures and their translation to Spanish - Morán Roa, Alberto; Méndez Castañeda, Gonzalo (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Despite past reticence about their form and content, the Lectures -notes by Immanuel Kant's students, recording his teaching on various subjects- are a valuable resource for Kantian studies. This can be corroborated by the value placed on them by their contemporaries, as well as by their role in presenting Kant's teaching, the evolution of his thought, the way in which key philosophical notions are conceptualized, and the theses with which they enrich the ideas presented in the written texts. Since the end of the 20th century, and especially since the 21st century, several of the Lectures have been translated into Spanish, offering important resources for the Spanish-speaking community. In this article we will present the contributions of these notebooks, both by Kant's contemporaries and today, and we will describe the existing translations into Spanish, mentioning the translation decisions of some key concepts, their most important contributions, and their academic reception.